2005
DOI: 10.1021/jp0502252
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Reduction on Rhenium(I) Complexes with Binaphthyridine and Biquinoline Ligands:  A Spectroscopic and Computational Study

Abstract: A number of rhenium complexes with binaphthyridine and biquinoline ligands have been synthesized and studied. These are [Re(L)(CO)3Cl] where L = 3,3'-dimethylene-2,2'-bi-1,8-naphthyridine (dbn), 2,2'-bi-1,8-naphthyridine (bn), 3,3'-dimethylene-2,2'-biquinoline (dbq), and 3,3'-dimethyl-2,2'-biquinoline (diq). This series represents ligands in which the electronic properties and steric preferences are tuned. These complexes are modeled using density functional theory (DFT). An analysis of the resonance Raman spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 67 publications
1
24
0
Order By: Relevance
“…The mean absolute deviations (MADs) of experimental versus calculated ṽ using Raman vibrational frequencies can be used to quantify how effectively the calculated optimized geometry has modeled the compound in question. The technique used to generate MADs has been described in the literature and is adopted here. Typically a MAD of less than 15 cm –1 is regarded as satisfactory, especially in the case of large, dynamic molecules such as the studied compound series. For every compound, a MAD of less than 15 cm –1 was attained and has been included with an associated scaling factor in Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…The mean absolute deviations (MADs) of experimental versus calculated ṽ using Raman vibrational frequencies can be used to quantify how effectively the calculated optimized geometry has modeled the compound in question. The technique used to generate MADs has been described in the literature and is adopted here. Typically a MAD of less than 15 cm –1 is regarded as satisfactory, especially in the case of large, dynamic molecules such as the studied compound series. For every compound, a MAD of less than 15 cm –1 was attained and has been included with an associated scaling factor in Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…The reason for this enhancement is that this normal mode, in which the CO ligands stretch and compress in phase, is one of the normal coordinates that shows distinct structural distortion on going from the ground to the resonant excited state (Fig. 1) [20,21]. This relationship between resonance Raman enhancements and ground-to excited-state structural displacements was first enunciated by Hirakawa and Tsuboi [19] and subsequently developed by others [22].…”
Section: The Fc State-resonance Raman Scatteringmentioning
confidence: 85%
“…This has been used in a study of the spectroscopy and DFT modelling of [Cu(phen)(PPh 3 ) 2 ] + [46]. The comparison between experimental and calculated vibration data was parameterised by the frequency mean absolute deviation (MAD) [21,[47][48][49] for the most intense bands (generally those of >20% the most intense feature). In general it is found that if the MAD is <10 cm −1 then other electronic parameters correlate well [21,46,47,50,51].…”
Section: Quantifying the Normal Coordinate And Calculated Raman Intenmentioning
confidence: 99%
“…The MADs were determined as 4-11 cm −1 , with an average of 6 cm −1 , which was deemed to be a good correlation. [34][35][36]…”
Section: Ground State Vibrational Spectroscopymentioning
confidence: 99%